2017
DOI: 10.5455/ijtrr.000000255
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aerobic Exercise on Physical Fitness and Fatigue in Children with Acute Lymphoblastic Leukemia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
3
0
6
Order By: Relevance
“…From secondary supported studies for our results, Abd El Bakya and Adel Elhakk [18] reported that there was a significant improvement in both physical fitness and fatigue levels in children who survived ALL with the inclusion of a 16-week aerobic exercise training program with a home exercise program. Moreover, Adamsen et al [22] showed that a high-intensity exercise program for 6 weeks led to an improvement in VO2 max by 16% in patients with cancer, including leukemia.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…From secondary supported studies for our results, Abd El Bakya and Adel Elhakk [18] reported that there was a significant improvement in both physical fitness and fatigue levels in children who survived ALL with the inclusion of a 16-week aerobic exercise training program with a home exercise program. Moreover, Adamsen et al [22] showed that a high-intensity exercise program for 6 weeks led to an improvement in VO2 max by 16% in patients with cancer, including leukemia.…”
Section: Discussionsupporting
confidence: 55%
“…According to San Juan et al [17] and Abd El Bakya and Adel Elhakkb [18], the patients of group A received aerobic exercises using a RAM model (770 CF) electronic treadmill (two sessions/week, with each session lasting from 20 to 35 min). The patients were started with at least 50% of maximum heart rate (HRmax), which was measured with 220 − age, and 70% HRmax at the end of the 12th week of the program.…”
Section: Treatment Procedures Aerobic Trainingmentioning
confidence: 99%
“…Latihan fisik ini bertujuan untuk mengatasi kelelahan yang diharapkan lebih efektif dan efisien waktu pada anak-anak yang mengalami kelelahan pada penderita LLA. Anak-anak juga memiliki kemampuan beradaptasi yang lebih baik terhadap pelatihan serta jaringan tubuh mereka yang lebih elastis dan lebih fleksibel dibandingkan pasien dewasa (Baky & Elhakk, 2017).…”
unclassified
“…Melalui program latihan aerobik ini dapat membantu suplai oksigen ke jaringan yang mengarah pada peningkatan kebugaran pernapasan, hal ini disebabkan oleh pengaruh senam aerobik terhadap fungsi pernapasan dan kapasitas kerja jantung. Hal tersebut diyakini sangat berpengaruh dalam mengatasi masalah fisik terkait kanker serta meningkatkan kualitas hidup anak-anak yang mengalami LLA (Baky & Elhakk, 2017).…”
unclassified
“…Resultados similares se encontraron en el estudio de diseño ensayo clínico controlado elaborado por Lam y colaboradores y realizado en China, que respalda los resultados encontrados en esta revisión integrativa ya que mostraron niveles estadísticamente significativos (p=0,010) más bajos de fatiga a los 9 meses después del inicio de un programa de ejercicios de estiramiento y relajación, ejercicios de fortalecimiento y resistencia, y ejercicios aeróbicos en interiores y exteriores, que incluyeron actividades físicas de intensidad baja a moderada; en niños y adolescentes de entre 9 y 18 años, diagnosticados con tumores sólidos y líquidos (178). De igual manera, el estudio de diseño prospectivo aleatorizado controlado elaborado por Baky y colaboradores, realizado en Egipto, informó niveles estadísticamente significativos (p=0,05) para la reducción de la fatiga, con un programa en el hogar de ejercicios aeróbicos de intensidad moderada definidos como ejercicio submáximo, rítmico y repetitivo de un gran grupo de músculos, durante el cual la energía necesaria es suministrada por el oxígeno inspirado mismo que tuvo una duración 16 semanas, en niños y adolescentes con edades comprendidas entre 8 y 16 años, con diagnóstico de leucemia linfoide aguda (179).…”
Section: El Uso Del Ejercicio Como Estrategia Y Sus Efectos En Las Di...unclassified